Physical Education Activities as Perceived by Conservative Bangsamoro Women - Angelo L. Gedoria; Bai Omayya P. Sumail; Solayha A. Sam; Sittie Rahema T. Daglok; Candao G. Daglok (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This quantitative-descriptive study aimed to determine the learning activities of the conservative Bangsamoro women in Physical Education activities, specifically, in terms of dance exercise, team sports, and the barriers affecting the learning activities of conservative Bangsamoro women in terms of sports attire, skills development in physical activities. The study’s respondents were female 3rd year students of AB Islamic studies. The study used a survey questionnaire to determine the learning activities of the Bangsamoro conservative women. The results showed that conservative Bangsamoro women generally expressed positive learning activities in dance exercise and team sports. In addition, the conservative Bangsamoro women consider sports attire a barrier in learning physical education, and generally agree that attire significantly influences their participation and performance in physical activities. Moreover, the respondents’ activities moderate to high levels of discomfort and challenges when engaging in physical activities due to religious and cultural constraints, which become barriers to full participation and skills development in physical education. It is concluded that while conservative Bangsamoro Women find their learning activities in physical education, particularly in dance exercise and team sports, beneficial and meaningful sports attire/uniform, and some cultural and religious limitations on attire pose a challenge, hindering their full participation and development in physical education activities. This calls for an inclusive and culturally sensitive policy that promotes participation and skill development in physical education to enhance the learning activities of Bangsamoro conservative women.